Origin of Cancers Clinical Perspectives and Implications of a Stem-Cell Theory of Cancer - Tu, Shi-Ming. (Cancer Treatment and Research,, 2010)
The theory of a stem-cell origin of cancer is neither ground breaking nor earth shattering. Many prominent investigators have established the foundation for this concept and performed the vital experiments to support its validity and merit. The purpose of this book is to illustrate how this theory may completely transform our current views and perspectives about cancer. It is anticipated that the variety of ramifications of a stem-cell origin of cancers will be embraced by the medical research community to bring new treatment modalities to the cancer patient. "The stem-cell theory of cancer has significant biologic and clinical consequences. Though components remain open to debate the fundamental observations are grounded in scientific experimentation. This text explains the conceptual aspects of cancer stem cells with an emphasis on the implications for our patients." - Steven T. Rosen, M.D. Series Editor .